EXPLORING THE PERCEPTION OF ONLINE GAME ADDICTION IN ADOLESCENTS: IDENTITY, MOTIVATION, AND SOCIAL INTERACTION PATTERNS: Eksplorasi Persepsi Kecanduan Game Online Remaja: Identitas, Motivasi Dan Pola Interaksi Sosial - Fadilah, Risydah; Lubis, Suaidah; Harianty, Widya; Sintyasari, Desi; Yanuar, Hendra; Taremica, Graris; Hermina, Mutia; Suri, Atikah; Khaliza, Dina; Maulana, Iqbal (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Technological developments have made online gaming a part of teenagers' lifestyles, but excessive use can trigger addiction (gaming addiction). This phenomenological qualitative study aims to explore the meaning of online gaming addiction among teenagers, its relationship with self-identity, motivation to play, and social interaction patterns. The research subjects were three individuals (aged 13 – 16 years) who played online games for more than three hours per day and were active at least four to five times a week, using purposive sampling techniques. Data were collected through observation and interviews with research respondents. The results showed that online games are perceived as a space for virtual identity construction, emotional regulation, and alternative social interaction. Adolescents with online gaming addiction experience shifts in self-identity, gaming motivations driven by challenge, stress avoidance, and the need for recognition, as well as significant changes in social interaction patterns, particularly reduced quality of family relationships. This study highlights that online gaming addiction affects not only individual behavior but also adolescents’ real-life social dynamics.